Molecular and microscopy detection of Pneumocystis jirovecii in hospitalized patients during the COVID-19 pandemic - Matouri, Roya; Aboutalebian, Shima; Nasri, Elahe; Sadeghi, Somayeh; Rostami, Soodabeh; Fakhim, Hamed; Ghafel, Safiyeh; Hosseini, Mahnaz; Mousavi, Somayeh; Rouhi, Faezeh; Pestechian, Nader; Mirhendi, Hossein (Frontiers in Medicine, 2023)
Early detection of Pneumocystis jirovecii as an opportunistic pathogen that may endanger predisposed persons, including COVID-19 patients, may help to choose the optimal management. This study investigated 585 COVID-19 patients who presented clinical and radiological evidence suggestive of respiratory diseases. Clinical specimens were examined by direct microscopy and nested PCR, and randomly selected positive PCR products were confirmed through DNA sequence analysis. Thirty-one samples were positive in P. jirovecii-specific nested PCR, while by direct microscopic tests, Pneumocystis was observed in 22 (3.76%) samples. Therefore, considering the result of PCR, a 5.3% prevalence of P. jirovecii-associated infections/colonization was rated. Males (61.7 %) and patients over 50 years old (75.6%) were more commonly affected than others, and malaise and fatigue (84%), and wheezing (75%) were the most common symptoms, followed by fever (40.48%) and dyspnea (39.51%). Among the PCP-positive patients, three cases had coinfection with Aspergillus fumigatus, A. flavus, and A. niger (each n=1), as documented by direct microscopy, culture, and species identification by PCR-sequencing. Pneumocystis pneumonia (PCP) is still a diagnostic challenge, and additional large-scale studies are needed to clarify the epidemiology of P. jirovecii in immunocompromised or COVID-19 patients.